Flood Simulation Utilizing HEC-HMS and HEC-RAS - Yousif, Yasameen T.; Hamdan, Ahmed N. A. (Civil Engineering Journal, 2026)
The substantial amount of rainfall leading to runoff in floodplain regions poses hazards to residents within these areas and surrounding zones; consequently, flood simulation is crucial for precise risk evaluation and the formulation of water utilization strategies. In this research, hydraulic and hydrological models, supported by Geographic Information Systems (GIS), were employed to simulate rainfall-runoff mechanisms in Wasit Governorate, central Iraq. A resolution of 30 m Digital Elevation Model (DEM) was supplied by the USGS, geospatially processed, and then imported into the Hydrologic Modeling System (HEC-HMS) at the Hydrologic Engineering Center. The runoff within the research area was estimated using the SCS-CN approach. In order to find the Curve Numbers (CN), a number of datasets were combined, including those pertaining to land use, land cover (LULC), and soil types. The HEC-HMS system was fed CN values obtained from GIS, which varied between 73.95 and 97.61. During the incident in November 2015, the Hydrologic Engineering Center's River Analysis System (HEC-RAS) was utilized to simulate floods using the runoff data resulting from HEC-HMS. Inundation maps were produced using RAS-Mapper within HEC-RAS, depicting flood depth and velocity through the study area. The flood model underwent calibration through comparison of the simulation results with satellite imagery for November 14, 2015. Using CSI, the hydrological factors Ia, Muskingum K, and X, and impervious % were adjusted using sensitivity analysis to achieve the greatest convergence between the model and satellite image. The result of CSI was 88.56%, (HR) was 96.31%, and (FAR) was 8.33%. The validation has been done for the calibrated parameters, and the results were compared with satellite imagery for April 3, 2019. The high level of concordance allowed for the final inundation map to be approved. The importance of measuring runoff for managing water resources effectively and reducing flood risks is highlighted by this study.